Beyond efficacy in water containers: Temephos and household entomological indices in six studies between 2005 and 2013 in Managua, Nicaragua - Arosteguí, Jorge (BMC Public Health, 2017)
BACKGROUND: A cluster-randomized controlled trial of community mobilisation for dengue prevention in Mexico and Nicaragua reported, as a secondary finding, a higher risk of dengue virus infection in households where inspectors found temephos in water containers. Data from control sites in the preceding pilot study and the Nicaragua trial arm provided six time points (2005, 2006, 2007 and 2011, 2012, 2013) to examine potentially protective effects of temephos on entomological indices under every day conditions of the national vector control programme. METHODS: Three household entomological indicators for Aedes aegypti breeding were Household Index, Households with pupae, and Pupae per Person. The primary exposure indicator at the six time points was temephos identified physically during the entomological inspection. A stricter criterion for exposure at four time points included households reporting temephos application during the last 30 days and temephos found on inspection. Using generalized linear mixed modelling with cluster as a random effect and temephos as a potential fixed effect, at each time point we examined possible determinants of lower entomological indicators. RESULTS: Between 2005 and 2013, temephos exposure was not significantly associated with a reduction in any of the three entomological indices, whether or not the exposure indicator included timing of temephos application. In six of 18 multivariate models at the six time points, temephos exposure was associated with higher entomological indices; in these models, we could exclude any protective effect of temephos with 95% confidence. CONCLUSION: Our failure to demonstrate a significant protective association between temephos and entomological indices might be explained by several factors. These include ecological adaptability of the vector, resistance of Aedes to the pesticide, operational deficiencies of vector control programme, or a decrease in preventive actions by households resulting from a false sense of protection fostered by the centralized government programme using chemical agents. Whatever the explanation, the implication is that temephos affords less protection under routine field conditions than expected from its efficacy under experimental conditions. TRIAL REGISTRATION: ISRCTN 27581154. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-017-4296-6) contains supplementary material, which is available to authorized users.